Strategi Komunikasi Pariwisata Melalui Instagram @PARIWISATANGAWI Sebagai Media Informasi Pariwisata Di Kabupaten Ngawi - Alferdo Kurniawan; Denik Iswardani Witarti (Cakrawala - Jurnal Humaniora, 2023)
Tourism is an important sector in the economic development of a region. In the digital era like now, social media has become an effective tool for promoting tourism destinations. Instagram, as one of the most popular social media platforms, has great potential to become an effective tourism information medium. This research aims to explain the tourism communication strategy used by the Instagram account @PariwisataNgawi in promoting Ngawi Regency as a tourism destination. This research uses qualitative methods to identify the type of content posted, hashtag use, interaction with users, and posting frequency. In addition, this research concludes that Instagram @PariwisataNgawi has succeeded in implementing an effective tourism communication strategy in promoting Ngawi Regency as a tourism destination. By making good use of social media, Ngawi Regency can continue to increase its tourism appeal and attract more tourists to visit this area. It is hoped that this research can provide valuable insight for local governments and related parties in developing their tourism communication strategies through social media.